UNILATERAL BREAST EDEMA DUE TO SUBCLAVIAN VEIN COMPRESSION - Bitencourt, Almir Galvão Vieira; Avelino, Eurípedes Barsanulfo de Paula; Zanella, Diogo; Marques, Elvira Ferreira (Mastology, 2017)
Unilateral breast edema may have different causes that vary from malignant to benign diseases. The knowledge of the main etiologies, associated to a detailed clinical examination and to radiological findings, is important in order to establish the correct diagnosis and determine the appropriate management of the patient. This article will report the case of a patient with lung cancer who developed unilateral breast edema; the main differential diagnoses will also be discussed